Graduation of medical students through multimodal clinical simulation: Process experience from a Peruvian university - Prialé, Alvaro (2022)
Introduction: Medical education has been affected by social isolation due to the pandemic, and the evaluation of clinical skills in students must opt ​​for options such as clinical simulation. Objective: to describe the evaluation of the degree exam for human medicine interns with multimodal clinical simulation. Clinical evaluation: The structured activity with multimodality from the methodology and location of the participants fulfilled the objective of evaluating and graduating interns. It was carried out through the presentation of case scenarios of two of the major specialties in the intern per student, carried out in a simulation office and a high-fidelity room occupying simulated patients, high-performance simulators, nurse/assistance, function software vital and technical simulation, all of them in person in addition to the student, and the juries remotely who, through observation first and then the support of the student, were able to evaluate performance through rubrics.